Effect of Plant Density and Nutrient Management on Yield and Economics of Maize (Zea mays L.) Hybrids - Biswas, S.; Debnath, S.; Saha, A. (International Journal of Bio-resource and Stress Management, 2022)
The field experiments wereconducted during kharif season (June to October)of both 2016 and 2017 to determine the effect of plant density and nutrient management on yield and economics of maize hybrids at Kalyani AB Block seed farm situated atLatitude 22o57/ N,Longitude 88o20/ E, West Bengal, India.The experiments were arranged at split-split plot design with three replication, two maize hybrids (Pioneer 3077 and Kaveri 50) were in main plot, two plant density (60×20 cm2 and 50×20 cm2) were in sub plot and three nutrient levels (Recommended Dose of Fertilizer i.e. 120:60:60 N:P2O5:K2O kg ha-1, Soil test crop response i.e. 170:60:68 N:P2O5:K2O kg ha-1 and Site Specific nutrient management i.e. 130:44:66N:P2O5:K2O kg ha-1 ) were in sub-sub plot. Result indicated that maize hybrid pioneer 3077 recorded higher grain yield, stover yield and net return and B:C ratio of maize than other hybrid. Higher plant density 50×20 cm2 produced significantly higher yield and economics of maize than lower plant density. Among the nutrient management, Soil Test Crop Response (STCR) was found significantly superior than others and recorded highest grain yield, stover yield and economics of maize. Soil Test Crop Response based nutrient management increased in grain yield was 24.26% over Recommended Dose of Fertilizer (RDF) and 12.29% over Site Specific nutrient management (SSNM).